2014
DOI: 10.1016/j.cub.2014.09.050
|View full text |Cite
|
Sign up to set email alerts
|

Nonpolitical Images Evoke Neural Predictors of Political Ideology

Abstract: SummaryPolitical ideologies summarize dimensions of life that define how a person organizes their public and private behavior, including their attitudes associated with sex, family, education, and personal autonomy [1, 2]. Despite the abstract nature of such sensibilities, fundamental features of political ideology have been found to be deeply connected to basic biological mechanisms [3–7] that may serve to defend against environmental challenges like contamination and physical threat [8–12]. These results inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
98
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 43 publications
4
98
2
Order By: Relevance
“…Although typical fMRI analyses are descriptive in nature and lack predictive power, new methods are emerging that try to find multiregional brain activity patterns that collectively predict a specific cognitive condition or individual characteristic (14)(15)(16)(17)(18)(19)(20). This is a particularly challenging task, given that, with fMRI data, the number of predicting variables is generally much higher than the number of observations, and hence there is a risk of producing either computationally intractable or strongly overfit models (15,21,22).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Although typical fMRI analyses are descriptive in nature and lack predictive power, new methods are emerging that try to find multiregional brain activity patterns that collectively predict a specific cognitive condition or individual characteristic (14)(15)(16)(17)(18)(19)(20). This is a particularly challenging task, given that, with fMRI data, the number of predicting variables is generally much higher than the number of observations, and hence there is a risk of producing either computationally intractable or strongly overfit models (15,21,22).…”
Section: Significancementioning
confidence: 99%
“…A new method has been suggested that tries to tackle this problem by using elastic-net (EN) regression. EN regression uses a mix of L1 and L2 regularization to prevent overfitting, while at the same time ensuring that the final model includes all of the relevant brain regions (14,15,21). This new method could potentially be applied to predict the MPC's "culpable" mental states based on a person's fMRI data.…”
Section: Significancementioning
confidence: 99%
“…At stake is a normative and practical issue-of whether a typical human reaction justifies us in drawing moral conclusions, something that, whether we like it or not, we all have a tendency to do. In particular, disgust plays a prominent role in the thinking of political and moral conservatives [Graham et al 2009;Ahn 2014]. Lord Devlin [1968] famously wrote that deeply felt and widespread disgust is a reliable indicator of the limits of what can be tolerated in any society in order to preserve basic social conventions.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with a study of Madsen [6] showing a role of serotonin in dominance behaviour, biology has increasingly become a focus of explanation in understanding ideas related to political and other social attitudes. Among dispositional factors related to broad biological processes that have captured recent attention are neural structures [7][8][9][10] and cognitive processes [11] including physiological response to threats [12], facial expression processing [13] and sensitivity to disgust.…”
Section: Introductionmentioning
confidence: 99%